PENGARUH KONFLIK PERAN GANDA DAN PENYESUAIAN DIRI TERHADAP STRES KERJA PADA IBU YANG BEKERJA - Burhani Puteri, Nabilah Assakinah; Anwar, Hilwa; Irdianti, Irdianti (Program Studi Psikologi Universitas Malahayati, 2024)
Abstrak Ibu yang bekerja memiliki tanggung jawab dan peran yang banyak sehingga memerlukan penyesuaian diri. Konflik peran ganda yang tinggi dapat menyebabkan ibu yang bekerja mengalami stres kerja, dan kemampuan penyesuaian diri yang baik dapat membantu meminimalisir tingkat stres kerja. Penelitian ini bertujuan untuk menguji pengaruh konflik peran ganda dan penyesuaian diri terhadap stres kerja pada ibu yang bekerja. Sampel pada penelitian ini adalah ibu bekerja yang memiliki anak sulung usia 0-6 tahun, usia pernikahan di bawah 10 tahun, bekerja di luar rumah dan bekerja di bawah instansi. Subjek pada penelitian ini berjumlah 60 orang ibu yang bekerja. Penelitian ini menggunakan metode kuantitatif dan menggunakan teknik analisis data regresi linear berganda. Hasil penelitian ini menunjukkan bahwa terdapat pengaruh positif konflik peran ganda dan pengaruh negatif penyesuaian diri terhadap stres kerja pada ibu yang bekerja. Hal tersebut menandakan bahwa semakin tinggi konflik peran ganda maka tingkat stres kerja semakin tinggi. Sedangkan semakin tinggi penyesuaian diri maka tingkat stres kerja semakin rendah. Penting bagi ibu bekerja untuk meningkatkan kemampuan penyesuaian diri agar menurunkan stress kerja dan tekanan akibat konflik peran ganda. Kata Kunci: Ibu Bekerja, Konflik Peran Ganda, Penyesuaian Diri, Stres Kerja AbstractWorking mothers have many responsibilities and roles that require good adaptability. High level of work-family conflict can cause working mother to experience job stress, and self adjustment can help to minimize job stress levels. This study aims to examine the effect of work-family conflict and adjustment to job stress in working mother. The sample in this study were working mothers who had 0-6 years old first child, under 10 years marriage age, worked outside house and worked in institute. Subject in this study were 60 working mothers. This study uses quantitative methods and multiple linear regression data analysis techniques. The results of this study indicate that there is a positive effect of work-family conflict and a negative effect of self adjustment to job stress in working mother with a significant value (p=0,00). This indicates that the more higher work-family conflict, the more higher level of job stress. Meanwhile, the more higher self adjustment, the more lower level of job stress. The benefit of this research is for working mothers to become a reference in increasing insight regarding multiple role conflicts and work stress in order to be able to adjust. The benefits of this research for institute are to become a reference in reducing work stress levels for women workers who have multiple roles. It is important for working mothers to increase their ability to adapt in order to reduce stress and pressure due to multiple role conflict Keywords: Working Mother, Work-Family Conflict, Self Adjustment, Job StressWorking mothers have many responsibilities and roles that require good adaptability. High level of work-family conflict can cause working mother to experience job stress, and self adjustment can help to minimize job stress levels. This study aims to examine the effect of work-family conflict and adjustment to job stress in working mother. The sample in this study were working mothers who had 0-6 years old first child, under 10 years marriage age, worked outside house and worked in institute. Subject in this study were 60 working mothers. This study uses quantitative methods and multiple linear regression data analysis techniques. The results of this study indicate that there is a positive effect of work-family conflict and a negative effect of self adjustment to job stress in working mother with a significant value (p=0,00). This indicates that the more higher work-family conflict, the more higher level of job stress. Meanwhile, the more higher self adjustment, the more lower level of job stress. The benefit of this research is for working mothers to become a reference in increasing insight regarding multiple role conflicts and work stress in order to be able to adjust. The benefits of this research for institute are to become a reference in reducing work stress levels for women workers who have multiple roles. It is important for working mothers to increase their ability to adapt in order to reduce stress and pressure due to multiple role conflict